2002
DOI: 10.1097/00005768-200212000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise on physiological and psychological variables in cancer survivors

Abstract: Low- and moderate-intensity aerobic-exercise programs were equally effective in improving physiological and psychological function in this population of cancer survivors. Aerobic exercise appears to be a valuable and well-tolerated component of the cancer-rehabilitation process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
152
1
9

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(170 citation statements)
references
References 21 publications
8
152
1
9
Order By: Relevance
“…These prior studies focused primarily on aerobic activity. Previous randomized exercise intervention studies specifically among breast cancer survivors have reported that physical exercise such as walking, 14 aerobic exercise, 8,9,17 Tai Chi, 29 and upper extremity exercise 30 had beneficial effects on QOL. For instance, the Rehabilitation Exercise for Health After Breast Cancer (REHAB) trial 9 assessed the effects of a 15-week aerobic exercise intervention on postmenopausal breast cancer survivors and the results showed beneficial effects on changes in happiness, self-esteem, fatigue, and several subcomponents of overall QOL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These prior studies focused primarily on aerobic activity. Previous randomized exercise intervention studies specifically among breast cancer survivors have reported that physical exercise such as walking, 14 aerobic exercise, 8,9,17 Tai Chi, 29 and upper extremity exercise 30 had beneficial effects on QOL. For instance, the Rehabilitation Exercise for Health After Breast Cancer (REHAB) trial 9 assessed the effects of a 15-week aerobic exercise intervention on postmenopausal breast cancer survivors and the results showed beneficial effects on changes in happiness, self-esteem, fatigue, and several subcomponents of overall QOL.…”
Section: Discussionmentioning
confidence: 99%
“…Aerobic exercise training had beneficial effects on cardiopulmonary function, 8,9 physical performance, 10,11 insulin sensitivity, 12 immune function, 13 chronic fatigue, 10,14,15 depression, 16 and QOL 8,9,14,17 in breast cancer survivors. However, the effects of weight training in breast cancer survivors on physiological and psychological benefits are unknown.…”
mentioning
confidence: 99%
“…Exercise leads to improvements in pulmonary function and cardiovascular endurance but also in muscle strength [29] and muscle weakness in cancer survivors can be influenced by regular exercise [4,6,29,33]. Therefore, postcancer rehabilitation is of high value comprising a long-term benefit [3] and physical activity constitutes an important component to posttreatment rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…Several of these programs were offered to individuals in group format and these reported improvement in quality of life, physical functioning and fatigue in cancer patients during primary treatment [3][4][5][6][7][8][9][10] and after completion of initial treatment [11][12][13][14]. Recently, interest has been growing in patients' experience with training within groups.…”
Section: Introductionmentioning
confidence: 99%